Effect of Indomethacin and Dimethylsulfoxide on the oxidative status of humor aqueous in ocular burn - Semih Altan; Feray Altan; Zeki Ogurtan (Revista Científica, 2025)
The study aims to investigate the efficacies of dimethyl sulfoxide (DMSO) and indomethacin on the oxidative status in the aqueous humor of rabbits’ eyes with experimentally induced hydrofluoric acid ocular burns. For this purpose, thiobarbituric acid (TBARS) and total antioxidant status (TAS) were measured. Seventy– two male New Zealand rabbits were allocated into four groups, each containing 18 rabbits (Group D, I, DI, and C). After general anesthesia, 2% hydrofluoric (HF) acid was dropped into the right eye for 60 s, creating a chemical burn. Solution of 40% DMSO (4 drops of QID) and 0.1% indomethacin (4 drops of QID) were used alone and in combination. At the end of the follow–up periods (2, 7, and 14 treatment days), animals were euthanized, and the humor aqueous was collected from the burned eyes by anterior chamber paracentesis. The TBARS and TAS levels were assessed using enzyme–linked immunosorbent assay (ELISA) in aqueous humor. On days 7 and 14, the TBARS levels in the aqueous humor of group D differed significantly from those in the other groups (P<0.05). Additionally, TAS values were considerably higher in groups D and C compared to groups I and DI (P<0.05). This study is thought to be a model for further studies in ocular diseases such as chemical eye burns, which may result in impaired ocular healing due to oxidative stress. DMSO could decrease oxidative stress and improve tissue healing of chemical eye burns.